Factors determining the expenditure of Lao tourist on Luang Prabang tourism during the epidemic situation of COVID-19: https://doi.org/10.69692/SUJMRD080270 - BOUNPATHAPH, Latsamy; UNTONG, Akarapong; WAIAPHA, Yutthakarn (Souphanouvong University Journal Multidisciplinary Research and Development, 2022)
The purpose of this research was to study the factors that determine the expenditure of Lao tourist on Luang Prabang tourism during the epidemic situation of COVID-19. It was developed on a model based on Engel's law and applied Multiple Classification Analysis (MCA) to analyze the data to forecast tourist spending based on their personal attributes. The results showed that certain personal characteristics of tourists influenced what Lao tourists spent on tourism in Luang Prabang at a significant level of 0.01, with the highest spending on Luang Prabang tourism. This was found to be a tourist who earns more than of 601 USD per month or more, are male, aged 40 years and over, married, and from Vientiane Capital. They have an education level of a Bachelor's degree or higher, have a private business career, and traveling to Luang Prabang for the 5th time or more and will spend about than 150.49 USD per person per day on Luang Prabang tourism. Therefore, tourists with such characteristics are a marketing target that concerned parties must prioritize in marketing.